انسان کی صنفیں : قرآن اور تفاسیر کی روشنی میں: Human genders in the light of the Qur’an and its Commentaries - Dr. Hafiz Hasan Madani (AL-IDRAK JOURNAL, 2023)
Transgender Protection Rights Act 2018, implemented in Pakistan, has enacted legislation for the addition of gender, the third gender of human beings. Many objections are being raised by political, social and religious circles on this act. After which this law is discussed in the Council of Islamic Ideology, the Federal Sharia Court and the Legislative Assemblies of Pakistan. The most important objection to this Act is with regard to the third gender of human, on which the Qur'anic verses and its commentaries are presented here.